DIURETIC STUDIES ON LEMON GRASS TEA FROM CYMBOPOGON CITRATUS (DC) STA PF IN RAT - Mirza, Maryam; Askari, Abid; Yaqueen, Zahra; Ahmad, Zamir; Qadri, R B (Biological Sciences - PJSIR, 2001)
The safet y of lemon grass tea prepared from Cymbop ogon cilratus (DC) Stapf. (lemon grass) was eval u a ted i n rats. The extract was ad mi ni stered for 6 weeks intragas tri cally and produ ced n o adverse effects a fter its use. No morph om etri cal or hi stol ogical changes were noticed i n th e vi t al organs of th e test and control ani m al s. Besides no bi ochemi cal ch an ges were noticed i n t he blood and u ri ne of test rats un der our ex peri men tal conditi on s. Th e resu l t s were com parab l e wi th standa rdgreen tea. It was diureti c i n action.